2000
DOI: 10.1034/j.1600-051x.2000.027010763.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis in dental plaque samples from children 2 to 12 years of age

Abstract: The purpose of this study was to detect the presence of Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis in plaque samples from 104 children, collected from their toothbrushes using a polymerase chain reaction (PCR). The age range of all subjects was 2-12 years. 21, 73 and 10 children with healthy gingiva, gingivitis and periodontitis respectively were selected. Plaque samples were collected from all erupted teeth sites using a sterile toothbrush. The mean concentration of DNA recovered from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 26 publications
3
66
1
4
Order By: Relevance
“…DNA extraction from dental plaques and saliva was performed as previously described (Okada et al 2000, Kignel et al 2005. Briefly, 10 mL of dental plaque suspension or 1 mL saliva were centrifuged for 5 min at 10,000 rpm.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA extraction from dental plaques and saliva was performed as previously described (Okada et al 2000, Kignel et al 2005. Briefly, 10 mL of dental plaque suspension or 1 mL saliva were centrifuged for 5 min at 10,000 rpm.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…(Madmujar et al 1990, Krajden et al 1989, Nguyen et al 1995, Loster et al 2006, De Sousa et al 2006, Souto & Colombo 2008, Silva et al 2009) have reported that the oral cavity can be a reservoir for H. pylori, making treatment difficult and exposing the individual to a higher risk of gastric reinfection. However, Okada et al (2000), Dye et al (2002) and Olivier et al (2006) have characterised the bacterium in the oral cavity as being mainly transient. Despite this, these authors do not discard the hypothesis that an association between the presence of the bacteria in the stomach and mouth may exist.…”
Section: Detection Of H Pylori In Saliva and Dental Plaque By Southementioning
confidence: 99%
“…Dental plaque was collected from all erupted teeth by brushing with a sterile toothbrush for 1 min, using a previously described method (Okada et al, 2000). Plaque adhering to the toothbrush was removed by washing several times in a tube of sterile distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…P. gingivalis is uncommon or found in low numbers in healthy individuals and those with gingivitis, while it is more frequently detected in those with more destructive forms of disease (3). The pathogen is considered to be mainly associated with adult periodontitis (4), and we previously found that P. gingivalis organisms were rarely present in the oral cavities of healthy children (5).…”
Section: Introductionmentioning
confidence: 99%
“…52/2). Subjects with clinically healthy gingiva, as well as those with gingivitis and periodontitis, were studied and classified as follows (5). Those with an absence of inflammation, no bleeding on brushing, and no radiographic bone loss were regarded as having clinically healthy gingiva and classified as the healthy group (n = 134), while subjects with mild to moderate inflammation at more than 1 site, as determined by gingival index (15), and no radiographic bone loss were classified as the gingivitis group (n = 239), and those with attachment loss of greater than 3 mm at 1 site or more among four teeth were defined as the periodontitis group (n = 27).…”
Section: Subjectsmentioning
confidence: 99%